Do Clouds have Politics? Reflections on Aesthetic Encounter, Nature, and Power - Dunn, Chris (The Nordic Journal of Aesthetics, 2025)
This paper considers contemporary academic discourse concerning the relationship between nature and the political. The main question it addresses is the significance of aesthetic encounter with nature, specifically if and to what extent nature’s display can be understood as providing a vantage or connection to something beyond human power relations. It does so by drawing from some reflections in the philosophy of technology and environmental philosophy concerning the nature of the artifactual and the artifactuality of nature. The title itself is derived from Langdon Winner’s essay Do Artifacts Have Politics? In considering this question, Winner undertakes an analysis of New York City underpasses and can be seen as a precursor to political ecology. This paper will thus consider the limits of a shared understanding within political ecology of nature as inherently and inseparably political. It distinguishes between socially totalizing and socially transcendent views. It incorporates phenomenological reflections and responds to certain key philosophical texts such as Bill McKibben’s The End of Nature, Eric Katz’s criticisms of ecological restoration, Stephen Vogel’s Thinking Like a Mall and long-standing relevant contemplations ranging from Thoreau to the Tao Te Ching. This topic is increasingly pertinent in an era of climate change and other global environmental crises.